Short Communication: Fishing inside Qeshm Island's MPA, Atortuous approach - VAHID CHAMANARA; EHSAN KAMRANI; MOSTAFA ZAHIRINIA; KATHLEEN SCHWERDTNER MANEZ (Smujo International, 2016)
Abstract. Chamanara V, Kamrani E, Zahirinia M, Máñez KS. 2016. Short Communication: Fishing inside Qeshm Island’s MPA, A tortuous approach. Nusantara Bioscience 8: 169-173. Incremental pressure of population growth in coastal areas has led to loss in many mangrove areas. Although these areas are fish nursery grounds and are very important in stock assessments, there is no accurate and up-to-date available data about them. In this research, the catch data in the Qeshm Island Marine Protected Area (MPA) of Iran was investigated using 11 stake nets. Totally, 81 specimens belonging to 69 genera and 63 families were caught, which majority of them were discarded. The commercial fish were young which were mostly smaller than LM50. In case of White Pomfret as well, only 15.3% of the caught individuals were in the legal catch size. Hence, this catch composition would be a potential threat to fish stocks. The major numerical and weight based specimens were Dussumieria acuta (10.05%) and Arius maculatus (5.9%), respectively. Containing 7 species, the Clupeidae was the most abundant family in the catch composition. Eventually, total annual catch by abovementioned stake nets within the mangrove forests in the Qeshm Island marine protected area was estimated to be 186.77-188.75 tonnes, approximately.